China’s minorities without written scripts : The case of education access among the Dongxiang - Wang, Jiayi and Postiglione, Gerard A. (Journal of Asian Pacific Communication, 2008)
The Chinese state sees language as an essential determinant in ethnic minority schooling. The use of minority language as a medium of instruction is viewed as a way to increase attendance rates and strengthen socialization into a national ideology. However, the policies differ for those ethnic miorities with or without a commonly used written script. Among the minorities without a script are the 300,000 strong Dongxiang, an ethnic group with the lowest level of literacy and school access in China. There is virtually no systematic research on the role of language in school access for Chinese minority groups without a written script. In particular, there is a lack of analysis of the Dongxiang (and similar groups without a written script) learning and school discontinuation. This research aimed to identity the major difficulties in school based learning for the Dongxiang speaking children. Specifically, it explores local perspectives on how language and other factors are related to school enrolment and achievement. In order to accomplish this, the research combined a variety of data gathering methods, including survey questionnaires, open ended interviews, in-depth interviews, field visits, observations, and case studies to analyze the difficulties of language transition faced by Dongxiang ethnic minority children. The results reveal that although native language does not directly cause schoolchildren to discontinue their studies, it has an important indirect influence, especially on the girls. The research results also show that Dongxiang ethnic minority schoolchildren in the early years of schooling generally cannot understand their teachers’ Chinese teaching, which results in poor school performances, a decline of interest in learning, a frustrated sense of achievement, and a decline in self-respect. Many students drop out as part of a vicious cycle that sees a reproduction of poor conditions for learning.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTA3NS9qYXBjLjE4LjIuMDRwb3M